2016
DOI: 10.1021/acs.chemmater.6b00397
|View full text |Cite
|
Sign up to set email alerts
|

Band Alignments, Valence Bands, and Core Levels in the Tin Sulfides SnS, SnS2, and Sn2S3: Experiment and Theory

Abstract: Tin sulfide solar cells show relatively poor efficiencies despite attractive photovoltaic properties, and there is difficulty in identifying separate phases, which are also known to form during Cu2ZnSnS4 depositions. We present X-ray photoemission spectroscopy (XPS) and inverse photoemission spectroscopy measurements of single crystal SnS, SnS2, and Sn2S3, with electronic-structure calculations from density functional theory (DFT). Differences in the XPS spectra of the three phases, including a large 0.9 eV sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
163
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 192 publications
(199 citation statements)
references
References 92 publications
33
163
0
Order By: Relevance
“…The superior photocatalytic performance of the ZnO–Sn 2 S 3 core–shell structure is attributable to the band relation of the heterostructure. Notably, Sn 2 S 3 is a narrow-bandgap semiconductor with a reported electron affinity of approximately 3.56 eV [17], whereas ZnO is an n-type wide-bandgap semiconductor with a reported electron affinity of 4.35 eV [28]. These data may provide reliable references to approximately estimate the relative band edge positions of the two semiconductors.…”
Section: Resultsmentioning
confidence: 99%
“…The superior photocatalytic performance of the ZnO–Sn 2 S 3 core–shell structure is attributable to the band relation of the heterostructure. Notably, Sn 2 S 3 is a narrow-bandgap semiconductor with a reported electron affinity of approximately 3.56 eV [17], whereas ZnO is an n-type wide-bandgap semiconductor with a reported electron affinity of 4.35 eV [28]. These data may provide reliable references to approximately estimate the relative band edge positions of the two semiconductors.…”
Section: Resultsmentioning
confidence: 99%
“…We presented novel anodization protocol and photo-electrochemical results for anodic TiO 2 nanotubes grown with different diameter sizes (21,35, 56 and 95 nm) utilized as highly ordered n-type conductive scaffold for inorganic chromophore (Sn-S-Se). While downscaling the nanotube diameter significantly increased the number of nanotubes per square unit and thus the active surface area increased as well, we found that the photo-electrochemical response was identical and thus independent of the TiO 2 diameter nanotube size, but it correlated with the thickness of the nanotube layers.…”
Section: Discussionmentioning
confidence: 99%
“…[39,43,44,47] Binding energies of S 2p 3/2 (162.7 eV) and S 2p 1/2 (163.9 eV) seen in Figure 6b are also within the range of values reported for 2H-MoS 2 . [39,40,43,44,[47][48][49]51,52] Additionally, weak doublets at 161.8 and 163.3 eV as well as 163.9 and 165.1 eV were assigned to SnS [80] and CS bonding, respectively. Carbon and oxygen were present in multiple chemical environments, as revealed by their broad peaks ( Figure S2b,c, Supporting Information).…”
Section: Compositionmentioning
confidence: 99%